Regulation of anaerobic fermentation for producing short-chain fatty acids from primary sludge in WWTPs by different alkalis. (1st December 2021) - Wang, Jian; Liu, Guo-hua; Shao, Yuting; Zhang, Qian; Wei, Qi; Luo, Fangzhou; Sun, Wenzhuo; Liu, Shuai; Liu, Yuchen; Zhang, Jingbing; Qi, Lu; Wang, Hongchen
Abstract: Carbon source production from primary sludge in wastewater treatment plants (WWTPs) via anaerobic fermentation process has been paid more attention. However, slow hydrolysis rate and low yield of short-chain fatty acids (SCFAs) limited its application. This study aimed at improving the anaerobic fermentation efficiency of primary sludge by alkali regulation (NaOH, Na2 CO3 and Ca(OH)2 ), and revealing the mechanism. Results showed that three kinds of alkalis allowed enhancing hydrolysis and acidification, and reducing methane production in the anaerobic fermentation process of primary sludge. The Na2 CO3 regulation contributed to highest yield and productivity of SCFAs, reaching 1626 mg COD/L and 0.189 g COD/g VSS at 4th day, respectively. Microbial community structure analysis indicated that the relative abundance of fermentative microbial community was improved in the alkali regulation system, where methanogenic archaea was effectively inhibited. The continuous flow experiment further verified that the Na2 CO3 regulation could steadily increase yield of SCFAs in the anaerobic fermentation process of primary sludge, and the yield was also the highest among three kinds of alkali regulation. Highlights: The yield and productivity of short-chain fatty acids were improved by alkali regulation. Alkali regulation promoted both chemical and microbial hydrolysis of primary sludge. The methanogenic archaea was inhibited by adding the degree of alkalinity. The Na2 CO3 regulation enabled the highest productivity of short-chain fatty acids.